Lenong Sebagai Salah Satu Media Komunikasi Dalam Dakwah Dan Pembinaan Pemuda Kemang Jakarta Selatan (Studi Kasus Manggar Kelape, Kemang Jakarta Selatan) - Asriyani Sagiyanto (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
Lenong is one of the arts and culture that express a reality in the community and serves alsoas a medium of communication. Lenong Betawi arts can also serve as a medium tocommunicate a moral message or propaganda that is common in the eyes of society. In thejourney of this art is the result of a process of acculturation and interaction from the beginningis heavily influenced by Chinese culture, Arabic and Portuguese.Manggar kelape Betawi is a studio that is always consistent in art conservation Betawiculture, one of which is lenong Betawi arts. Coaching in the studio has a very important rolein educating and making changes in the behavior of self, as well as a positive character,especially young people in Kemang, South Jakarta to be better. Demoralization of youngchildren today one of them due to environmental factors. This is what makes manggar Kelapeset up an art studio Betawi pursued through non-formal education that is art with variousforms of development, especially the youth in order to become a better person.